The electronic word-of-mouth in rural tourism: the case of schist villages - Santos, Marta Isabel Henriques Parente dos (2018)
The rural area has undergone many transformations in terms of functionality and identity resulting in an attempt to grow tourism to improve environmental, economic, social and cultural promotion, preservation and revitalization of these areas when compared to urban spaces that are much more developed. In this way, tourism in rural areas (TER) in Portugal is seen as a driving force for the community development and its entire surrounding. Over the years, technologies have been constantly evolving. This has been reflected in people’s decision-making process and, consequently, how they purchase their products and services. Tourists increasingly use online reviews made by other users in their travel planning, which contain descriptive comments and/or a rating system, named as electronic word-of-mouth (eWOM). In this way, this study intends to understand the evolution of the eWOM in rural tourism, by studying the main characteristics that influence consumers’ satisfaction. To that end, the content of the comments and quantitative classification of Schist Villages lodgings on the platforms of TripAdvisor and Facebook were studied, using extraction, polarity and frequency techniques as well as the SPSS program for the analysis.